Investigation of Affordable Technologies for Real-Time See-Through Various Indoor Surfaces and Walls - Qurban Ali Memon; Selama Tekleab; Jood Albedwawi; Fatima Alantali; Alyazia Ateeq Aldhaheri (Advances in Technology Innovation, 2025)
Wireless scanning for detecting objects behind various surfaces or walls in indoor settings has garnered significant interest recently. This study presents experimental results on several widely accessible, affordable, and portable see-through technologies. The technologies evaluated include a radio frequency (RF) device, a chip-sized multiple-input and multiple-output (MIMO) radar, an ultra-wideband sensor, and a motion sensor. These can be used either as standalone transceivers or mounted on unmanned aerial vehicles (UAVs) to extend their range, particularly for emergencies in high-rise buildings. Tests on various wall and surface materials show that RF and Wi-Fi devices can detect objects through wood, glass, and plasterboard, but metal and concrete significantly block or limit signal penetration. The results suggest that affordable see-through technologies need to improve their performance against concrete and metals.